Option to revoke and regulation of local utilities - Michele Moretto; Paola Valbonesi (Fondazione Eni Enrico Mattei (FEEM), 2000)
We study a long-term relationship between a risk-neutral firm that has been delegated to manage a local utility project and a regulator that has always the option-to-revoke the delegation. We show that when the threat of revocation is credible and the cost of exercising it is not too high, the "cooperative" equilibrium is an efficient solution which guarantees the utility with an appropriate level of return. The regulation timing consists of an endogenous regulatory lag where the regulation has a fixed-price nature followed by a period of rate-of-return regulation in which the firm is motivated to adjust its output price downward to avoid revocation. We also show that excessive revocation costs make the firm an unregulated monopolist with an infinite regulatory lag.
Keywords: C73; L33; L51; 330; Public utilities; option-to-revoke; stochastic games; Regulierungstheorie; Versorgungswirtschaft; Privatwirtschaft; Theorie